‘Inside’ the Tradition of the Śilpaśāstras: Introductory Remarks on the Historical Study of Indian Texts on Art - Jaskūnas, Valdas (Acta Orientalia Vilnensia, 2004)
The article sets up to discuss the relevance of the tradition of art texts (śilpaśātras) to the understanding of Indian art. This tradition has been dealt with for almost two hundred years since the first translation of text fragments from the treatises on Indian architecture by Ram Raz. The recent researches in the field threw a new light upon the aspects of provenance and function of shilpashastric texts, as well as their relationship with the extant works of art. The context-based approach to Indian art, avoiding the mistakes made when the textual and art history studies were carried out simultaneously but very rarely coming into contact and enriching one another, enables us to explore anew the role of these texts within the tradition of Indian art. Nevertheless, the manner in which the conceptual systems of śilpaśātras and the artistic tradition actually interact - how thought and action affect one another - is not a question simple to answer. The main reason for lacking research on this interaction is a rather stylistic approach, which dominates art history and pays too little attention to understanding the idea and provenance of śilpaśātras. The present research does not look for an unambiguous answer to the question concerning the role of shastric tradition in the overall artistic culture; rather it attempts to frame a preliminary working hypothesis for further investigation with a more coherent gaze at one of most undeservedly neglected spheres of Indian intellectual culture, namely, shilpashastric tradition and the role it played in the intellectual history of India.